Reinforced thermoplastic natural rubber hybrid composites with Hibiscus cannabinus, L and short glass fiber – Part I: Processing parameters and tensile properties - Anuar, Hazleen; Wan Busu, Wan Nazri; Ahmad, S. H.; Rasid, Rozaidi (SAGE Publications, Inc, 2008)
Hybrid composite of thermoplastic natural rubber (TPNR) reinforced with Hibiscus cannabinus, L fiber (kenaf fiber: KF) and short glass fiber (GF) were prepared via melt blending method using internal mixer, at various temperatures, speed and time. TPNR matrix is a blend of polypropylene (PP), liquid natural rubber (LNR) and natural rubber (NR) at a ratio of 70 : 10 : 20. Processing parameters were determined from the tensile strength based on fiber content with 50 : 50 ratios of GF and KF. Using the optimum processing parameters, tensile test was carried out for reinforced TPNR–KF–GF hybrid composites (0–20% by volume), with and without addition of silane coupling agent and maleic anhydride grafted polypropylene (MAPP). The result of tensile strength has shown that the increasing in kenaf fiber content substantially reduced the tensile strength and modulus. Scanning electron microscopy (SEM) has shown that the composite, with coupling agent or compatibilizer, promotes better fiber–matrix interaction.